PENGARUH PEMBERIAN AROMA TERAPI SEREH (LEMONGRASS) TERHADAP KUALITAS TIDUR IBU MENOPAUSE DI POSBINDU TUAH MANDIRI BALOI PERMAI, KOTA BATAM - Yutha Febria; Aryaneta, Yenni (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2026)
Sleep quality is a condition that reflects an individual's ability to sleep and obtain adequate rest according to their needs. During the menopausal transition, disturbances such as difficulty falling asleep, frequent awakenings, and early morning waking are common and distressing. Poor sleep quality in menopausal women contributes to physical health problems, including decreased concentration and an increased risk of falls, and also leads to psychosocial issues that reduce overall quality of life. In some cases, it may contribute to depressive symptoms. Non-pharmacological approaches, such as progressive muscle relaxation and aromatherapy, are commonly used to improve sleep quality. These methods are considered cost-effective, practical, and less likely to cause side effects or dependence compared to pharmacological treatments. One type of aromatherapy that may be beneficial is lemongrass aromatherapy. This study aims to determine the effect of lemongrass aromatherapy on the sleep quality of menopausal women. The study used a pre-experimental design with a one-group pretest-posttest approach. A total of 32 menopausal women participated using an accidental sampling technique. Sleep quality was measured using the Pittsburgh Sleep Quality Index questionnaire. Data analysis using the Paired T-Test showed a significance value of 0.001, which is less than 0.05. This indicates that lemongrass aromatherapy has a significant effect on improving sleep quality among menopausal women at Tuah Mandiri Baloi Permai Posbindu, Batam City, in 2025. The findings suggest that this intervention can be recommended as a simple, safe, and accessible complementary therapy to support better sleep and enhance well-being in menopausal populations overall. Keywords: Aromatherapy Lemongrass, Sleep Quality, Menopausal Women